Society of masses and democracy - Miró Quesada Rada, Francisco (2021)
The masses have played an important role in the history of modern industrialized. Its appearance in the phase of the industrial capitalism generated economic dynamic unpublished and a deep relationship with democracy. Democracy organizes the power around the freedom, equality, the dignity and the self-rule and incorporates the masses in their practices. In that way their marked decisive participation is noted on the right to vote, the political parties and the active participation of citizens. However the society of masses is reorganized with the technological changes and forces him to new forms of coexistence.